Female Sex as a Risk Factor for Ischemic Stroke and Systemic Embolism in Chinese Patients With Atrial Fibrillation: A Report From the China‐AF Study. Issue 19 (2nd October 2018) - Lan, Di‐Hui; Jiang, Chao; Du, Xin; He, Liu; Guo, Xue‐Yuan; Zuo, Song; Xia, Shi‐Jun; Chang, San‐Shuai; Wen, Song‐Nan; Wu, Jia‐Hui; Ruan, Yan‐Fei; Long, De‐Yong; et al.
Abstract : Background: Previous studies have provided conflicting results as to whether women are at higher risk than men for thromboembolism in the setting of atrial fibrillation (AF). We investigated whether women with AF were at higher risk of ischemic stroke in the China‐AF (China Atrial Fibrillation Registry) Study. Methods and Results: A total of 19 515 patients were prospectively enrolled between August 2011 and December 2016 in the China‐AF Study. After exclusion of patients receiving anticoagulation or ablation therapy, 6239 patients (2574 women) with results from at least 6 months of follow‐up were used for the analysis. Cox proportional hazards models were performed to evaluate whether female sex was an independent risk factor for thromboembolism after multivariate adjustment. The primary outcome was the time to the first occurrence of ischemic stroke or systemic embolism. After a mean follow‐up of 2.81±1.46 years, 152 female patients reached the primary outcome, as compared with 172 male patients. Crude incidence rates of thromboembolism between women and men were of borderline statistical significance (2.08 versus 1.68 per 100 patient‐years, P =0.058). After multivariable analysis, female sex was not independently associated with an increased thromboembolism risk (hazard ratio 1.09, 95% confidence interval 0.86‐1.39). There was no significant difference in thromboembolism risk by sex stratified by age and presence or absence of risk factors ( P for interaction all >0.1). Conclusions: Although crude incidence rates of thromboembolism were higher in Chinese female patients with AF compared with male patients, female sex did not emerge as an independent risk factor for thromboembolism on multivariate analysis. Clinical Trial Registration: URL: http://www.chictr.org.cn/ . Unique identifier: ChiCTR‐OCH‐13003729.